THE EDUCATORS' CAPACITY IN THE IMPLEMENTATION OF INTEGRATIVE HOLISTIC EARLY CHILDHOOD DEVELOPMENT (NUTRITION-HEALTH, STIMULATION, CARE, PROTECTION WELFARE) - Netti Herawati (Universitas Panca Sakti Bekasi, 2024)
The research purposes are obtain a general overview of the capacity of educators in providing Holistic Integrative Early Childhood Development, namely Pengembangan Anak Usia Dini Holistik Integratif (PAUD HI) and the factors that influence the capacity of educators in PAUD HI. The total number of educators who participated in this study was 117,632 respondents. The total data used for analysis after going through the data cleaning process was 117,616. Respondents came from 34 provinces and 425 districts/cities. The number of respondents is Formal PAUD (TK, RA) 48.6% and Non-Formal PAUD (KB, SPS, TPA, and PAUD) 51.4%. The sampling technique used in the data collection process is Accidental Sampling. Respondents are educators who are willing to be respondents in this study. The total number of items in instrument are 42 items. The results are: a) average capacity of educators in PAUD HI is still relatively low (58.5) with a minimum reference score for passing PAUD HI training being 70.0, b).The capacity of educators in PAUD HI is clearly influenced by Teaching Experience, Personal Development, and Integrative Holistic Principles in PAUD HI. Length of teaching has the greatest influence, followed by self-development (number of training courses attended), and knowledge of PAUD HI principles, c).The PAUD HI capacity of Formal ECE’s educators (60.69) is significantly higher than the capacity of Non-formal ECE’s educators (56.37), d). Collaboration with ECE in implementing PAUD HI is still limited to the following areas: (1) education services (78.2%); (2) health sector (72.4%); (3) the teacher professional organizations (69.4%).